Teamwork skills pada peer consultant writing center dan mahasiswa pengguna jasanya - Gennesia Vebriana; Elisabeth Rukmini (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. Writing centers (WC) as a writing consultation would help students complete their scientific writing and improve their non-technical skills. This study aimed to determine the effect of WC on students' teamwork abilities. Data Collection Methods. This research is a cross-sectional descriptive and explorative study. The quantitative method measured students' teamwork utilizing the Teamwork Skills Questionnaire at three points of collection. The qualitative method collected data from in-depth interviews. Both types of data came from peer-consultants (PC) and users of WC services. Data Analysis. Quantitative data analysis used the repeated measure of one-way ANOVA, and qualitative data analysis used the content analysis. Results and Discussion. We found that the p-value is 0.857 for the PC and 0.044 for the user from the data analysis. Results showed a significant increase in the user's teamwork ability. Although the quantitative results of the PC were not significant, from the qualitative analysis, PCs explained that the WC could train teamwork indirectly through communication skills, adaptation, leadership, and collaboration. Conclusion. The teamwork skills that students have before and after the WC program was categorized as high. WC had a subtle influence on the teamwork ability of the PC and its users. We suggest that the university elaborate the WC as one of the students' services.